Pengaruh Pelatihan, Motivasi Berprestasi dan Kompensasi Terhadap Kinerja Guru - Mayasari, Mayasari; Nasution, Abdul Gani; Saragih, Darmansyah; Naibaho, Agus Maihot; Hasibuan, Baharuddin Yusuf; Zainuddin, Ahmad; Nasti, Nilawati; Safrida, Safrida; Tarigan, Nur. M. Ridha (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study has the aim to determine the effect of training, achievement motivation and compensation on teacher performance at Madrasah Aliyah Negeri 1 Langsa City. The approach used in this research is a quantitative approach. Data collection is done through library research and questionnaires. The sample in this study amounted to 54 teachers who served in Madrasah Aliyah Negeri 1 Langsa City. The conclusions of the research conducted include: 1) Training has a positive but not significant effect on teacher performance at Madrasah Aliyah Negeri 1 Langsa City, as the coefficient value tcount < ttable, which is 0.105 < 1.674 at significant 0.917 > 0.05. Which means that under H0 is accepted while H1 is rejected because the effect is still in the insignificant category. Although the results of this study show a non-significant effect, the more dominant fact shows that teacher training activities can increase knowledge and skills which have a positive impact on teacher performance. 2) Achievement motivation has a positive and significant effect on teacher performance at Madrasah Aliyah Negeri 1 Langsa City, as the coefficient value tcount > ttable, which is 19.956 > 1.674 at significant 0.000 < 0.05. Which means that the research hypothesis H0 is rejected and H2 is accepted. This means that there is a positive and significant contribution to achievement motivation on teacher performance. 3) Training compensation has a positive and significant effect on teacher performance at Madrasah Aliyah Negeri 1 Langsa City, as the coefficient value tcount < ttable, which is 4.143 > 1.674 at significant 0.000 > 0.05. Which means that the research hypothesis H0 is rejected and H3 is accepted. Therefore, the compensation program given to teachers will provide high enthusiasm for teachers in teaching. 4) Training, achievement motivation and compensation simultaneously affect teacher performance at Madrasah Aliyah Negeri 1 Langsa City. This is evidenced by the significant value of 0.000 < 0.05 and the value of Fcount > Ftable (1201.835 > 3.17). The influence is symbolized by R (correlation). The magnitude of the coefficient of determination (R Square) is R Square 0.986 or equal to 98.6% meaning that the variables of training, achievement motivation and compensation simultaneously (together) affect teacher performance variables.